The Adolfsson-Björnsson Activity Scale (ABAS) Improves Description of Patient Characteristics - Adolfsson, Lars; Lundin, Per; Hallgren, Hanna Björnsson (Archives of Clinical and Biomedical Research, 2022)
Background and purpose: Age and gender have been regarded important for surgical decision making and used as inclusion criteria for clinical trials. Individual demands and level of activity have been less considered. A self-administered scale, defining subjectively assessed level of activity involving the upper extremities was therefore developed. The primary purpose of this study was to present the scale. Secondarily to investigate its reliability and correlation with age and gender. Patients and Methods: A scale with 8 categories ranging from extremely demanding to non-demanding activities, separated according to hand dominance, was constructed. Reliability testing was performed on 103 healthy individuals of both genders with a wide age range (20-86). 241 patients, median age 58 years (range 18-97), with different upper extremity injuries completed the scale. Participants were instructed to mark activities representative for their normal activity level. Correlation with age and gender was then investigated using Spearman Correlation Coefficient (SCC). Results: The level of activity ranged from 1, corresponding to minimal use of the arm, to 8 defined as elite sports. For test-retest Intraclass Correlation Coefficient (ICC) was 0.89 for the dominant and 0.90 for the non-dominant arm. Correlations between gender, age and level of activity were weak. Interpretation: The scale was found reliable and feasible to use. Age and gender were weakly correlated with level of activity and patients with low and high activities found in all ages and both genders. The activity scale allows improved description of patients included in clinical trials and can aid in treatment decision making but is primarily not intended for measurement of treatment outcome.